MIGRATING HERITAGE: CULTURAL DIALOGUE, IDENTITY AND CITIZENSHIP IN EUROPE - Innocenti, Perla (Acta Museologica Lithuanica, 2015)
This article introduces a wider study of the role of cultural and heritage networks and how they can help institutions and their host societies to manage the tensions and realise the opportunities arising from migration. It also addresses the shifts and continuities, tensions and crisis that characterise the European project and its cultural dimension today. A reflection on cultural heritage networks in an age of migration is followed by a description of the overall research focus and interdisciplinary methodology. An overview of three case studies selected from a larger pool is provided in the article, which is concluded by a coda on cultural networks and policy implications.
Keywords: migrating heritage; cultural networks; European identity; cultural information policies; models of musealisation; sociology of organisation